Nexus of governance, macroeconomic conditions, and financial stability of banks: a comparison of developed and emerging countries - Saif Ullah; Atta Ullah; Mubasher Zaman (Financial Innovation, 2024)
Abstract The study aims to explore the impact of governance and macroeconomic conditions on financial stability in developed and emerging countries. The study sample comprised 122 countries from 2013 to 2020, and a comprehensive set of variables was used to construct the financial stability index (FSI). The results of the two-step system GMM analysis, robust with D–K regression, indicate that interest rate, GDP growth, voice and accountability, political stability and absence of violence/terrorism, government effectiveness, regulatory quality, and control of corruption have a positive and statistically significant impact on financial stability. However, inflation, money supply, and the rule of law have adverse and insignificant effects on financial stability. Notably, the findings vary between developed and emerging countries due to differences in governance and macroeconomic conditions and their role in financial stability. The study concludes that regulatory governance and macroeconomic conditions are crucial for financial stability. These outcomes are significant for central banks, academia, and policymakers, as they emphasize the need for stable financial systems and sustainable, balanced growth through governance and macroeconomic conditions.